A Vladimir Propp Analysis of The Cursed Pocket Watch - Putri, Julie Abiya; Misrita, Misrita (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study analyzes the short story The Cursed Pocket Watch using Vladimir Propp’s eight character types to explore how traditional narrative roles are adapted within a modern psychological horror context. The analysis identifies Laila as the hero, the bullies as villains, and the haunted hut as the donor, among other character functions. The study highlights the dual role of the pocket watch as both helper and false hero, illustrating the complexity of magical objects in contemporary tales. Findings reveal how Propp’s framework remains relevant by accommodating symbolic representations, such as the abstract “princess” representing peace and acceptance. This paper demonstrates the flexibility of Propp’s theory for analyzing modern stories that address themes of bullying, isolation, and unintended consequences of power. Suggestions for future research include integrating psychological perspectives to enrich the understanding of character roles and thematic development in contemporary narratives.